Pokémon. Sun & Moon. 4 - Kusaka, Hidenori; Turnage, Bryant (VIZ Media, LLC, 2019)
Sun wants to learn the Z-Move but needs help from Captain Kiawe who has been attacked by Team Skull. Then, Sun needs to find a Z-Ring and prove himself to Island Guardian Tapu Lele.